Pectoralis Major Tear with Retracted Tendon: How to Fill the Gap? Reconstruction with Hamstring Autograft and Fixation with an Interference Screw - L. Baverel; K. Messedi; G. Piétu; V. Crenn; F. Gouin (Case Reports in Orthopedics)
Rupture of the pectoralis major tendon is considered an uncommon injury and a significant number of ruptures are missed or diagnosed late, leading to a chronic tear. We report an open reconstruction technique and its outcomes in a case of chronic and retracted PM tear. At the last follow-up (12 months), the patient was pain-free, with a visual analogic scale at 0 all the time. He was very satisfied concerning the cosmetic and clinical results. The constant score was 93%, the SST value 95%, and the Quick DASH score 4.5. MRI performed one year postoperatively confirmed the continuity between PM tendon and graft, even if the aspect of the distal tendon seemed to be thinner than normal PM tendon. The excellent clinical outcomes at one-year follow-up suggest that PM tear with major tendon retraction can be reliably reconstructed with hamstring autograft, using a bioabsorbable screw to optimize the fixation device. This technique has proven its simplicity and efficiency to fill the gap.